Answer:
x = -1 , y = -4
Explanation:
Solve the following system:
{13 x = -2 y - 21 | (equation 1)
-15 x = 2 y + 23 | (equation 2)
Express the system in standard form:
{13 x + 2 y = -21 | (equation 1)
-(15 x) - 2 y = 23 | (equation 2)
Swap equation 1 with equation 2:
{-(15 x) - 2 y = 23 | (equation 1)
13 x + 2 y = -21 | (equation 2)
Add 13/15 × (equation 1) to equation 2:
{-(15 x) - 2 y = 23 | (equation 1)
0 x+(4 y)/15 = -16/15 | (equation 2)
Multiply equation 2 by 15/4:
{-(15 x) - 2 y = 23 | (equation 1)
0 x+y = -4 | (equation 2)
Add 2 × (equation 2) to equation 1:
{-(15 x)+0 y = 15 | (equation 1)
0 x+y = -4 | (equation 2)
Divide equation 1 by -15:
{x+0 y = -1 | (equation 1)
0 x+y = -4 | (equation 2)
Collect results:
Answer: {x = -1 , y = -4